Mycoplasma arginini Cellulitis, Tenosynovitis, and Arthritis in Kidney Transplant Recipient, Slovenia, 2024 - Tjaša Vivoda; Tereza Rojko; Barbara Kokošar Ulčar; Katja Strašek Smrdel; Andraž Celar Šturm; Darja Keše; Tina Triglav; Željka Večerić Haler (Emerging Infectious Diseases)
Mycoplasma arginini is a bacterium primarily found in animals and is seldom reported in human infections. We identified M. arginini infection in a severely immunocompromised kidney transplant recipient in Slovenia. Clinicians should be aware of M. arginini’s potential as a pathogen in immunocompromised persons with animal contact.